Eutectic Combinations as a Pathway to the Formation of Substrate‐Based Au‐Ge Heterodimers and Hollowed Au Nanocrescents with Tunable Optical Properties. Issue 16 (14th April 2014) - Sundar, Aarthi; Farzinpour, Pouyan; Gilroy, Kyle D.; Tan, Teng; Hughes, Robert A.; Neretina, Svetlana
<x xml:space="preserve">Abstract</x> Pairs of immiscible elements with deep eutectics are used to synthesize periodic arrays of heterodimers and hollowed metal nanocrescents. In the devised route, substrate‐immobilized Au or Ag nanostructures act as heterogeneous nucleation sites for Ge adatoms. At elevated temperatures the adatoms collect in sufficient quantities to transform each site into a AuGe liquid alloy which, upon cooling, phase separates into elemental components sharing a common interface. The so‐formed Au‐Ge and Ag‐Ge heterodimers exhibit a complex morphology characterized by a noble metal nanocrescent which partially encapsulates one end of the Ge domain. Through the use of a selective etch the Ge component is removed, leaving behind a periodic array of hollow noble metal nanocrescents on the surface of the substrate. Optical characterization of both the heterodimers and nanocrescents indicates that the presence of Ge gives rise to a relative blue‐shift in the localized surface plasmon peak, a result that is in stark contrast to the red‐shifts typically observed when plasmonic nanostructures are in contact with a dielectric medium. Simulations are used to both rationalize the observed shift and show the potential for deriving unexpected behaviors when semishell‐like noble metal structures are in contact with high permittivity dielectric mediums.